2014
DOI: 10.1038/srep05268
|View full text |Cite
|
Sign up to set email alerts
|

Stable acetate production in extreme-thermophilic (70°C) mixed culture fermentation by selective enrichment of hydrogenotrophic methanogens

Abstract: The control of metabolite production is difficult in mixed culture fermentation. This is particularly related to hydrogen inhibition. In this work, hydrogenotrophic methanogens were selectively enriched to reduce the hydrogen partial pressure and to realize efficient acetate production in extreme-thermophilic (70°C) mixed culture fermentation. The continuous stirred tank reactor (CSTR) was stable operated during 100 days, in which acetate accounted for more than 90% of metabolites in liquid solutions. The yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…For both the incubation temperatures, the presence of BES and shaking at 100 rpm had a positive influence on acetate Average acetate production at an incubation temperature of 60 • C (1739.44 mg L −1 ) was more than two-folds higher than the acetate production at 45 • C (775.68 mg L −1 ). Previous studies have also shown the prominent effect of temperature on acetate production [4,12,51]. For both the incubation temperatures, the presence of BES and shaking at 100 rpm had a positive influence on acetate production.…”
Section: Selection Of Influential Factorsmentioning
confidence: 67%
See 3 more Smart Citations
“…For both the incubation temperatures, the presence of BES and shaking at 100 rpm had a positive influence on acetate Average acetate production at an incubation temperature of 60 • C (1739.44 mg L −1 ) was more than two-folds higher than the acetate production at 45 • C (775.68 mg L −1 ). Previous studies have also shown the prominent effect of temperature on acetate production [4,12,51]. For both the incubation temperatures, the presence of BES and shaking at 100 rpm had a positive influence on acetate production.…”
Section: Selection Of Influential Factorsmentioning
confidence: 67%
“…Average acetate production at an incubation temperature of 60 °C (1739.44 mg L −1 ) was more than two-folds higher than the acetate production at 45 °C (775.68 mg L −1 ). Previous studies have also shown the prominent effect of temperature on acetate production [4,12,51]. For both the incubation temperatures, the presence of BES and shaking at 100 rpm had a positive influence on acetate Average acetate production at an incubation temperature of 60 • C (1739.44 mg L −1 ) was more than two-folds higher than the acetate production at 45 • C (775.68 mg L −1 ).…”
Section: Selection Of Influential Factorsmentioning
confidence: 76%
See 2 more Smart Citations
“…10 All these aspects signicantly increase the costs of pure culture fermentation compared to mixed culture based industrial fermentation. 11,12 So, propionic acid production in MCF becomes an attractive route. 10 Anaerobic digestion (AD) consists of multiple steps including hydrolysis, acidogenesis, acetogenesis, and methanogenesis in MCF.…”
Section: Introductionmentioning
confidence: 99%